Pattern Recognition: Age-Specific Features of Fundamental Movement Skills Formation in Elementary School Students - Yunak, Iryna; Ivashchenko, Olha; Nosko, Mykola; Nosko, Yulia (Physical Education Theory and Methodology, 2022)
The purpose of the study was to determine the age-specific features of fundamental movement skills formation in elementary school students. Materials and methods. The study participants were boys aged 7 to 10 (24 boys aged 7; 28 boys aged 8; 35 boys aged 9; 36 boys aged 10). The children and their parents or legal guardians were fully informed about all the special aspects of the study and all the parents or legal guardians gave their consent thereto. The study protocol was approved by the Ethics Committee of the University. The features of teaching 7–10-year-old boys to throw a ball at a vertical target were investigated. The proficiency level in throwing exercises in class was assessed using an alternative method (“performed”, “failed”), the probability of the exercise performance was calculated (p = n/m, where n is the number of successful attempts, m is the total number of attempts). A method of algorithmic instructions was used in teaching boys aged 7 to 10. The study materials were processed by IBM SPSS 20 statistical analysis software. A discriminant analysis was conducted. Results. It was established that the first canonical function explains 64.5% of the variation in results, while the second one does 34.4%, which indicates their high informativity (r1 = 0.762; r2 = 0.652). The materials of the canonical function analysis show the statistical significance of the first and second canonical functions (λ1 = 0.236; р1 = 0.001; λ2 = 0.5633; р2 = 0.001). The first and second functions have a high discriminative ability and value in interpretation with respect to the general population. Conclusions. The discriminant analysis made it possible to determine the age-specific features of throwing skills formation in boys aged 7 to 10; answer the questions to which extent the differences in the effectiveness of skills formation in boys aged 7 to 10 are significant; which motor tasks are the most specific to boys aged 7, 8, 9, 10; which class an object belongs to based on the values of discriminant variables. It was established that the level of proficiency in exercise 4 “Throwing a ball forward-upward standing with the left side to the throwing direction” has the greatest effect on the process of throwing movement skills formation in boys aged 7 to 10. For boys aged 8 to 10, such an exercise is “Throwing a ball forward-upward standing feet apart”, and for boys aged 9 to 10, such an exercise is “Throwing a ball at a target 3 m away”.